Effectiveness of Couple Classes in Increasing Breastfeeding Rates and Preventing Breast Engorgement - Ayesha Hendriana Ngestiningrum; Nuryani Nuryani (Knowledge Dynamics, 2025)
Background: Exclusive breastfeeding (EBF) faces significant barriers, particularly in the first 7 days postpartum, primarily due to a lack of knowledge and skills about lactation among mothers and their partners. Couple classes have been proposed as a potential solution, as they provide lactation education to both mothers and their partners from pregnancy onward. This study aimed to evaluate the effectiveness of couple classes in enhancing breastfeeding rates and preventing breast milk stagnation during the early postpartum period. Methods: A quasi-experimental design with a posttest control group was used, targeting third-trimester pregnant women. The sample consisted of pregnant women who met the inclusion criteria, along with their husbands, who lived together and consented to participate. Exclusion criteria included husbands who worked out of town, those who did not attend all sessions, and those who experienced emergencies during pregnancy, childbirth, or postpartum. A total of 25 participants were assigned to each group through simple random sampling. The intervention group received couple class education, which was delivered online via WhatsApp Groups, along with direct assistance within the first 7 days postpartum. This support lasted for one month. The control group received standard care according to the PMB’s (Praktik Mandiri Bidan or Independent Midwife Practices) SOP (Standard operational procedure). Posttests were conducted on the seventh day postpartum. Breastfeeding rates and the occurrence of breast milk engorgement were assessed using a checklist. Statistical analysis was performed using the chi-square test to compare differences between the groups. Results: A significant difference in breastfeeding rates during the first 7 days was observed between the two groups (p = 0.034). Additionally, there was a significant difference in the prevention of breast milk engorgement (p = 0.017). Conclusions: Couple classes effectively increase breastfeeding rates and prevent breast engorgement, with online materials providing an efficient and impactful method of support.